Dynamics of the spatial electron density distribution of EUV-induced plasmas. (2nd October 2015) - van der Horst, R M; Beckers, J; Osorio, E A; Banine, V Y
Abstract: We studied the temporal evolution of the electron density distribution in a low pressure pulsed plasma induced by high energy extreme ultraviolet (EUV) photons using microwave cavity resonance spectroscopy (MCRS). In principle, MCRS only provides space averaged information about the electron density. However, we demonstrate here the possibility to obtain spatial information by combining multiple resonant modes. It is shown that EUV-induced plasmas, albeit being a rather exotic plasma, can be explained by known plasma physical laws and processes. Two stages of plasma behaviour are observed: first the electron density distribution contracts, after which it expands. It is shown that the contraction is due to cooling of the electrons. The moment when the density distribution starts to expand is related to the inertia of the ions. After tens of microseconds, the electrons reached the wall of the cavity. The speed of this expansion is dependent on the gas pressure and can be divided into two regimes. It is shown that the acoustic dominated regime the expansion speed is independent of the gas pressure and that in the diffusion dominated regime the expansion depends reciprocal on the gas pressure.